A Policy Implementation Model for Population Administration Digitalization: Lessons from the Implementation of Digital Identity - Susilawati Susilawati; Kusworo Kusworo; Mulyadi SP; Gatiningsih Gatiningsih (PT. Global Research Collaboration, 2026)
This study aims to analyze the implementation of the Digital Population Identity (IKD) policy, identify enabling and constraining factors, and develop a contextual policy implementation model. A qualitative case study approach was employed in Tulang Bawang Regency, Indonesia. Data were collected from XX informants consisting of government officials, implementing officers, and community members, complemented by field observations and document analysis. The data were analyzed thematically using NVivo 12 following the stages of data condensation, data display, and conclusion drawing. The findings indicate that the implementation of IKD in Tulang Bawang has not yet achieved optimal outcomes, as reflected in relatively low activation rates compared to provincial targets. Key challenges include limited human resource capacity, uneven digital infrastructure, and low levels of digital literacy among the population. The study also identifies enabling factors such as institutional commitment and inter-agency coordination. This study proposes the SUSI policy implementation model as an extension of the Van Meter and Van Horn model. The model introduces two additional analytical dimensions: digital leadership and digital inclusion. These dimensions are essential for understanding policy implementation in decentralized and digitally uneven governance contexts.